THE NEW NORMAL: HEART TALKS - ELIZABETH A/P M.ANTHONY; CHAN CHEE MING (2021)
Rather it is an attempt to provide individuals an avenue to pour out their grievance or joy. It merely highlights some of the concerns close to the hearts of people from all walks of life especially amidst the current COVID19 pandemic and how they deal with them. It encompasses diverse range of themes such as faith, hope, love, food, family, friendship, etc. The contents of this volume comprise three genres presented as separate parts; poems, prose and ‘mishmash’. The poems here are generally in stanzas but not bound to the strict conventions of meter, rhyme or alliteration. The prose is narratives written in short paragraph(s) to tell a story. Mishmash on the other hand is writings that do not belong to either the poem or prose genre.